Palm Terrace residence - Gordon, John C. (photographer):::Creator::::::::::::
Photograph shows a man and a woman standing on the lawn in front of a house. A car is parked on the curb in front of the house. Written on the bottom recto of the photograph: "'Palm Terrace,' residence of J.F. Hay, 52 South 12 St., San Jose, Calif."